Germplasm evaluation by cutting and grazing in small plots: Comparison of results - Gardner, Andrew L. (International Center for Tropical Agriculture, 1993)
The evaluation of pasture plants is complicated by the fact that no absolute yield exists with which experimental results can be compared. Evaluation techniques should therefore simulate as far as possible the conditions to be encountered on commercial farms, thus suggesting that modifications to evaluation methods will be necessary on a regional basis. Such considerations can be introduced at an early stage of germplasm evaluation. When cutting techniques are used to simulate grazing, care is required to ensure that no interaction between germplasm and defoliation method exists. In pure grass swards, defoliation by cutting would be acceptable, but for mixtures the selective effect of the grazing animal is preferable. While some transfer of fertility may exist when a series of plots are grazed together, this effect could be greatly exceeded if uneven grazing occurs over the area. Grazing by many animals for a short period of time is not representative of normal management and offers little advantage over a cutting technique. Only by measuring yield at critical times of the year can realistic grazing periods and grazing pressures be used.